(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article analyzes the traditional theatrical spaces at the expense of the introduction of cinematographic exhibitions introduction in São João del-Rei in the first half of the twentieth century. The buildings taken as samples for study are: Teatro Municipal, which started its activities in 1893, and the theater of the Clube Teatral Artur Azevedo, inaugurated in 1951. To carry out this analysis, architectural projects, photographs, newspapers and other documents were used in order to promote an understanding about the material creative processes of the discussed buildings, as well their transformations.